Pengaruh Literasi Keuangan, Gaya Hidup, dan Teman Sebaya Terhadap Perilaku Menabung Siswa SMAN 2 Depok - Imelda Apriliani; Aditya Pratama; Riswandi Riswandi (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Saving behavior is an essential aspect of developing students' ability to manage their finances wisely from an early age. However, the saving habits of some students remain relatively low and are influenced by various factors, including financial literacy, peer influence, and lifestyle. The inconsistent findings of previous studies regarding the relationships among these variables indicate the existence of a research gap that requires further investigation. Therefore, this study aims to analyze the effects of financial literacy, peer influence, and lifestyle on the saving behavior of students at SMAN 2 Depok and to examine the mediating role of lifestyle in these relationships. This study employed a quantitative approach using a causal associative research design. The population consisted of students at SMAN 2 Depok, with a sample of 140 respondents. Data were collected through a questionnaire using a Likert scale. Furthermore, the data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS 4 software. The findings revealed that financial literacy and peer influence had a positive and significant effect on students' saving behavior. In addition, financial literacy had a negative and significant effect on lifestyle, while peer influence had a positive and significant effect on lifestyle. On the other hand, lifestyle had no significant effect on saving behavior and was unable to mediate the effects of financial literacy and peer influence on students' saving behavior. These findings indicate that students' saving behavior is more strongly influenced by financial literacy and peer influence than by lifestyle.